Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1111/ejn.12393
|View full text |Cite
|
Sign up to set email alerts
|

The vomeronasal cortex – afferent and efferent projections of the posteromedial cortical nucleus of the amygdala in mice

Abstract: Registro de acceso restringido Este recurso no está disponible en acceso abierto por política de la editorial. No obstante, se puede acceder al texto completo desde la Universitat Jaume I o si el usuario cuenta con suscripción. Registre d'accés restringit Aquest recurs no està disponible en accés obert per política de l'editorial. No obstant això, es pot accedir al text complet des de la Universitat Jaume I o si l'usuari compta amb subscripció. Restricted access item This item isn't open access because of publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
51
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 99 publications
(159 reference statements)
9
51
0
Order By: Relevance
“…Previous works have reported basal forebrain projections to the Me (Cadiz-Moretti et al, 2016), the LOT (Grove, 1988) and PMCo (Gutierrez-Castellanos et al, 2014) similar to those described in this work. The projections arising from the diagonal band were previously reported with HRP injections in the Pir (Haberly and Price, 1978b).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Previous works have reported basal forebrain projections to the Me (Cadiz-Moretti et al, 2016), the LOT (Grove, 1988) and PMCo (Gutierrez-Castellanos et al, 2014) similar to those described in this work. The projections arising from the diagonal band were previously reported with HRP injections in the Pir (Haberly and Price, 1978b).…”
Section: Discussionsupporting
confidence: 89%
“…Regarding to the vomeronasal amygdala, the CxA received light projections from the PMCo, Me and AAD/AAV, and moderate ones from the BAOT ( Figure 8A ). Similar results were obtained with anterograde injections in the PMCo (Canteras et al, 1992; Gutierrez-Castellanos et al, 2014) and Me (Canteras et al, 1995; Pardo-Bellver et al, 2012), with minor differences regarding to the density of the labeling observed. These differences may be explained in part by the small size of the CxA injections in the present work, as well as different criteria to classify the labeling as moderate or scarce.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Unlike the ventral hippocampus, there was no significant relationship between PMCo 5-HT concentrations and anxiety-like behavior, and we are unaware of any evidence in the literature linking the PMCo to anxiety. Instead, this subregion of the amygdala appears to function primarily in olfactory signal integration (Gutierrez-Castellanos et al, 2014), with a role in directing appropriate chemosensory investigation behavior during rodent reproductive interactions (Maras and Petrulis, 2008). Thus, it appears most likely that increased anxiety-like behavior in 5,7-DHT treated rats was mediated by the ventral hippocampus and not the PMCo.…”
Section: Discussionmentioning
confidence: 99%
“…The NS of reptiles in total is considered homologous to the posterior medial cortical nucleus of the amygdala in rodents-a secondary vomeronasal center that is part of the vomeronasal amygdala (Gutiérrez-Castellanos et al, 2014;MartinezGarcía et al, 2002). The posterior cortical nucleus of the amygdala in female prairie (Microtus ochrogaster) and meadow (M. pennsylvanicus) voles expresses adult neurogenesis colocalized with estrogen receptor-α (Fowler et al, 2005), and neurogenesis increases in response to exposure to conspecific males (Fowler et al, 2002).…”
Section: Olfactory and Chemosensory Processingmentioning
confidence: 99%